The critical role of MLKL in hemorrhagic stroke and the therapeutic potential of its associated protein network - Wang, Yi; Xu, Moran; Zuo, Xiaoli; Wang, Sheng; Yu, Yong; Gao, Zhaobing; Qie, Jingbo; Jiang, Ye; Huang, Fang; Xia, Bingqing (Frontiers in Cell and Developmental Biology, 2025)
IntroductionMixed Lineage Kinase Domain-Like Protein (MLKL), as the executor of necroptosis and a critical factor in the inflammation, has been shown to be associated with the progression of hemorrhagic stroke. Studies identified MLKL is a promoting factor in this process, suggesting its potential as a therapeutic target to mitigate posthemorrhagic stroke damage. However, the mechanisms by which MLKL functions in the process of intracerebral hemorrhage (ICH)-induced damage remain unclear.MethodsHere, we explored the correlation between MLKL and pathological damage in ICH patients through histopathological staining and RT-qPCR. Furthermore, we established an intracerebral hemorrhage model by collagenase IV injection in WT and Mlkl-/- mice. Subsequently, we investigated the impact of MLKL knockout on ICH pathological damage through behavioral tests, Western blotting, and RT-qPCR. Finally, we performed a proteomic analysis via LC-MS/MS to explore the potential interacting proteins of MLKL in the progression of ICH.ResultsWe found that MLKL is highly expressed in the brain tissue of ICH patients and is positively correlated with the extent of injury. However, we found that Mlkl knockout alone was insufficient to fully reverse neuroinflammation and pathological damage. Although Mlkl knockout has a limited effect on alleviating ICH damage, proteomics results indicate that MLKL can mitigate changes in proteins associated with inflammation, metabolism, and coagulation pathways, suggesting that MLKL may exert its effects through these pathways.DiscussionIn summary, our results suggest that although MLKL is associated with the progression of ICH, single knockout of Mlkl is insufficient to fully reverse the pathological damage of ICH. Proteomic analysis indicates that co-targeting MLKL and its associated protein network may yield better therapeutic outcomes for hemorrhagic stroke.